Knowledge Mapping of Tourist Experience Research: Based on CiteSpace Analysis - Hongmei Guan; Taozhen Huang; Xin Guo (SAGE Open, 2023)
Tourist experience research has been increasing in practitioners and academics. The study collected 1,079 tourist experience related articles published in the Web of Science (WOS) core database to summarize research on tourist experience from 2007 to 2019 and to explore research hotspots and trends related to the topic. CiteSpace analysis was used from the selected 1,045 articles to identify and visualize the evolution of knowledge. The results revealed that the major disciplines for research tourist experience are Hospitality Leisure Sport Tourism disciplines. The most influential authors are mostly from high-yield institutions. The high-yield countries (regions) are in the USA, China, Australia, England and Italy. In addition, three hotspots research topics and contemporary trends are presented.